(3GdOdGFd aj TQM eG CZadg CHh YHjO hGHf bJjHI ef ZQjH GdMOjKs - (3bGSe Hf KGHJ Hf MRe GdYhaj GdSQbSWj, CHh eMeO,J (B302 (3g` s
(3ChdgG (B:s
(3hai MOjK GdfYeGf Hf HTjQ QMeg Gddg bGd ESJYedfi YeQ Hf GdNWGH Ch YKeGf Hf YaGf Ydi UObGJ SYOO gRje s
(3BNQgG (B:s
(3GdaQjfI hCgd GdTGe jJNPhf GdaQfjI Ydi UfYI cjQ GdRLGLjf jNJHQhf ajg GdafjI s
(3HgG fXGe GdJYbjHIs
(3Jhai GdeDda bHd EJeGeg hCced CHhg GdPi Jhai SfI (B313 (3bGd CHh Ydi GdbGdi Yfg Efg de jDda eKdg ai GdeZQH hbGd GHf GdaQVi hdG ai GdeTQbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B174s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GddZIs